2004
DOI: 10.1161/01.cir.0000145166.44942.e0
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C

Abstract: Background-Patients with suspected or confirmed non-ST-elevation acute coronary syndrome (ACS) constitute a large and heterogeneous group. Measurements of renal function such as serum creatinine and estimation of creatinine clearance carry independent prognostic information in this population. Cystatin C is a new and better marker of renal function than creatinine. The aim was therefore to evaluate the prognostic value of cystatin C in this population. Methods and Results-Cystatin C was analyzed on admission i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(79 citation statements)
references
References 19 publications
4
72
2
1
Order By: Relevance
“…Retrospective studies on existing cohorts very rapidly extended these findings to the entire population and in particular to the elderly. CysC was significantly associated with all cause mortality (209,(217)(218)(219)(220)(221)(222)(223), cardiovascular mortality (209, 217-219, 222, 223), myocardial infarction (209,224), cerebrovascular accident (209,225) and peripheral arterial disease (226). Whilst the association with all cause or cardiovascular mortality was found systematically, other authors failed to find relationships between CysC concentrations and non-coronary vascular accidents (218) mostly in middle-aged men (227).…”
Section: Future Perspectives For Cysc Applications Cysc As a Cardiovamentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective studies on existing cohorts very rapidly extended these findings to the entire population and in particular to the elderly. CysC was significantly associated with all cause mortality (209,(217)(218)(219)(220)(221)(222)(223), cardiovascular mortality (209, 217-219, 222, 223), myocardial infarction (209,224), cerebrovascular accident (209,225) and peripheral arterial disease (226). Whilst the association with all cause or cardiovascular mortality was found systematically, other authors failed to find relationships between CysC concentrations and non-coronary vascular accidents (218) mostly in middle-aged men (227).…”
Section: Future Perspectives For Cysc Applications Cysc As a Cardiovamentioning
confidence: 99%
“…Whilst the association with all cause or cardiovascular mortality was found systematically, other authors failed to find relationships between CysC concentrations and non-coronary vascular accidents (218) mostly in middle-aged men (227). These relationships between cardiovascular disease and increased CysC concentrations have been described both in cohorts or sub-groups of patients selected on the basis of a past history of cardiovascular disease (216,217,219,221,225,226) and in patients without cardiovascular history (220, 222-224, 228, 229). Some also consider that increased CysC values may be associated with morphological cardiac abnormalities, such as left ventricular hypertrophy or left ventricular dysfunction on echocardiography (228), functional abnormalities, such as heart failure (230), or poor exercise tolerance (231).…”
Section: Future Perspectives For Cysc Applications Cysc As a Cardiovamentioning
confidence: 99%
“…Biomarkers indicating myocardial dysfunction (eg, troponin, natriuretic peptides), renal dysfunction (eg, cystatin C), and inflammatory activity (eg, C‐reactive protein) are risk indicators of future cardiovascular events in healthy persons and in patients with established coronary heart disease (CHD) 2, 3, 4, 5. Higher levels of lipoprotein‐associated phospholipase A 2 (Lp‐PLA 2 ) activity have also been associated with an increased risk of coronary events in healthy elderly persons and in patients with stable CHD 6, 7, 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] The distinction between the 2 filtrating markers is pronounced in persons with eGFR greater than 60 mL/min (>1.00 mL/s); cystatin C level retains a strong association with cardiovascular risk in persons with eGFR greater than 60 mL/min (>1.00 mL/s), whereas creatinine level and eGFR have no significant association. 21 We previously showed that CKD, defined as creatinine clearance less than 60 mL/min (<1.00 mL/s), was associated with a 6-fold odds of poor exercise capacity in the Heart and Soul cohort compared with the highest creatinine clearance.…”
Section: Discussionmentioning
confidence: 99%
“…1 Increased serum cystatin C levels predict cardiovascular outcomes in outpatients with and without known coronary heart disease (CHD) and in patients presenting with acute coronary syndromes. [2][3][4][5][6] Cystatin C has a more linear association with cardiovascular mortality and adverse events than creatinine-based measurements. 5 A recent study defined elderly persons with increased cystatin C levels and estimated glomerular filtration rate (eGFR) greater than 60 mL/min (>1.00 mL/s) as having preclinical kidney disease and found this group to have increased risks of cardiovascular disease and incident chronic kidney disease (CKD).…”
Section: Introductionmentioning
confidence: 99%